2015
DOI: 10.1371/journal.pone.0136115
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression and Glucocorticoid Control of the Leptin Receptor in Fetal Ovine Lung

Abstract: The effects of endogenous and synthetic glucocorticoids on fetal lung maturation are well-established, although the role of leptin in lung development before birth is unclear. This study examined mRNA and protein levels of the signalling long-form leptin receptor (Ob-Rb) in fetal ovine lungs towards term, and after experimental manipulation of glucocorticoid levels in utero by fetal cortisol infusion or maternal dexamethasone treatment. In fetal ovine lungs, Ob-Rb protein was localised to bronchiolar epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…Tissue RNA was isolated from 15-mg samples of fetal lung (saline n = 6; 0.5 LEP n = 10; 1.0 LEP n = 7), and reverse transcription was carried out as described previously ( 29 ). TaqMan quantitative real-time-PCR was performed to measure mRNA abundance of target genes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue RNA was isolated from 15-mg samples of fetal lung (saline n = 6; 0.5 LEP n = 10; 1.0 LEP n = 7), and reverse transcription was carried out as described previously ( 29 ). TaqMan quantitative real-time-PCR was performed to measure mRNA abundance of target genes.…”
Section: Methodsmentioning
confidence: 99%
“…TaqMan quantitative real-time-PCR was performed to measure mRNA abundance of target genes. Samples were analyzed using a TaqMan 7900HT, and data were acquired and processed with Sequence Detector v.2.3 software (Applied Biosystems) ( 29 ). The ovine mRNA probes and primers for leptin, the active long form of the leptin receptor (Ob-Rb), and all forms of the leptin receptor (Ob-R), elastin, VEGF-A and VEGFR2, ACE, PPARγ, bovine PTHrP, and SP-A, SP-B, and SP-C, and bovine SP-D are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, leptin plays a two-fold role as a hormone and a cytokine. As a hormone, it modulates energy homeostasis by affecting energy expenditure, satiety and appetite [116][117][118]. As a pro-inflammatory adipokine, leptin is implicated, among others, in the modulation of gut microbiota composition through its receptors (LepRb) expressed in the submucosal intestinal zone, with increasing density of LepRb cells from the proximal tract to the colon [119].…”
Section: Inflammatory Cytokine Signalingmentioning
confidence: 99%
“…This is consistent with Slieker et al (94), who demonstrated that glucocorticoids increased both leptin mRNA and secretion in mouse adipocytes. Furthermore, Ob-Rb localisation in fetal ovine lungs, including alveolar type II pneumocytes, and an elevation in Ob-Rb mRNA levels in response to glucocorticoid treatment suggest a role for glucocorticoid control of leptin signaling in prenatal lung maturation (95). …”
Section: Glucocorticoids and Fpf Candidatesmentioning
confidence: 99%